Single Cell Protein Production using Yeast Isolates from Soy Factory Waste by Co-culture Method - Chintya Corin; Tri Ardyati (University of Brawijaya, 2014)
Nutrient content in soy waste able to allow growth of yeasts. Yeast isolates have potency to be used in the production of single cell protein. The research was carried out to study isolates for production of single cell protein using co-culture method and to determine the effect of co-culture method in protein content obtained. The isolates used were I2YP5K1, I2YP5K2, KYP6K1, KYP3K2, AYP6K1, AYP6K2, and AYP5K4. Steps used in this research were grown the yeast isolates in Yeast Malt Broth, assay of antagonist among yeast isolates, single cell protein production, and identification using API 20C AUX. Parameters measured were biomass, number of cells, and protein content. Design of research using two-way ANOVA with three replications. Isolates able to be used for co-culture method in the production of single cell protein were KYP3K2 (Saccharomyces cereviseae), AYP6K1, AYP6K2, and AYP5K4. Co-culture methods does not increase biomass and number of cells, however able to increase the protein content. Protein production by co-culture isolates KYP3K2 and AYP6K2 is highest than other co-culture isolates with protein content 1.31 mg / g. Key words : Co-culture, single cell protein, soy waste, yeast.